Finite Element Modeling of the Dynamic Response of Critical Zones in a Ballasted Railway Track - Punetha, Piyush; Maharjan, Krijan; Nimbalkar, Sanjay (Frontiers in Built Environment, 2021)
The critical zones are the discontinuities along a railway line that are highly susceptible to differential settlement, due to an abrupt variation in the support conditions over a short span. Consequently, these zones require frequent maintenance to ensure adequate levels of passenger safety and comfort. A proper understanding of the behavior of railway tracks at critical zones is imperative to enhance their performance and reduce the frequency of costly maintenance operations. This paper investigates the dynamic behavior of the critical zone along a bridge-open track transition under moving train loads using two-dimensional finite element approach. The influence of different subgrade types on the track behavior is studied. The effectiveness of using geogrids, wedge-shaped engineered backfill and zone with reduced sleeper spacing in improving the performance of the critical zone is evaluated. The numerical model is successfully validated against the field data reported in the literature. The results indicate that the subgrade soil significantly influences the track response on the softer side of the critical zone. The difference in vertical displacement between the stiffer and the softer side of a track transition decreases significantly with an increase in the strength and stiffness of the subgrade soil. The subgrade layer also influences the contribution of the granular layers (ballast and subballast) to the overall track response. As the subgrade becomes stiffer and stronger, the contribution of the granular layers to the overall track displacement increases. The mitigation techniques that improve the stiffness or strength of granular layers may prove more effective for critical zones with stiff subgrade than critical zones with soft subgrade. Among all the mitigation techniques investigated, the wedge-shaped engineered backfill significantly improved the performance of the critical zone by gradually increasing the track stiffness.